1991
DOI: 10.1346/ccmn.1991.0390412
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity of Siloxane Surfaces in Smectites as Revealed by Aromatic Hydrocarbon Adsorption from Water

Abstract: Abstract--The nature of the siloxane surface in smectites was investigated by measuring the adsorption of aromatic hydrocarbons from water by organo-clays. The organo-clays were prepared by replacing the hydrophilic, inorganic exchange cations of a series of smectites with the small, hydrophobic organic cation, trimethylphenylammonium (TMPA). Smectites with a range in charge densities were used that resulted in different TMPA contents in the organo-clays. Adsorption isotherms of benzene, alkylbenzenes, and nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
226
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(244 citation statements)
references
References 21 publications
17
226
0
1
Order By: Relevance
“…However, when sorption activation energies are 40-800 kJ/mol, chemisorption is posited. In our study, an activation energy of + 25.9 kJ/ mol was calculated from which, we hypothesized that sorption proceeded via physisorption in agreement with others' work (Dogan et al, 2006;Gü rses et al, 2006;Rodríguez et al, 2010), with denatonium sorbing to the clay surface in a manner similar to other hydrophobic quaternary cations ( Jaynes and Boyd, 1991). Experimental support for a physisorptive or cation exchange mechanism was provided via triplicate single-point sorption experiments as a function of background electrolyte ionic strength.…”
Section: Effect Of Temperaturesupporting
confidence: 82%
“…However, when sorption activation energies are 40-800 kJ/mol, chemisorption is posited. In our study, an activation energy of + 25.9 kJ/ mol was calculated from which, we hypothesized that sorption proceeded via physisorption in agreement with others' work (Dogan et al, 2006;Gü rses et al, 2006;Rodríguez et al, 2010), with denatonium sorbing to the clay surface in a manner similar to other hydrophobic quaternary cations ( Jaynes and Boyd, 1991). Experimental support for a physisorptive or cation exchange mechanism was provided via triplicate single-point sorption experiments as a function of background electrolyte ionic strength.…”
Section: Effect Of Temperaturesupporting
confidence: 82%
“…It has previously been demonstrated that polycondensation reactions of the silanol groups into irreversible siloxane groups are catalyzed by the inclusion of ZPO (Oubaha et al 2003). The result is a significant increase in siloxane bonds which are well-known to be hydrophobic (Jaynes and Boyd 1991). The underlying mechanism that causes increased hydrophobicity for 100% compared to 50% hydrolysed materials is similar to that explained above for increased ZPO content.…”
Section: Surface Characterisation-effect Of Oxygen Plasma Modificationmentioning
confidence: 53%
“…[16,23] The cation exchange capacity (CEC), which directly correlates with the negative-layer charge density, is an important determiner of the distance between adjacent interlayer cations (the spatial density). Achieving an appropriate distance can allow the material to act as a molecular sieve for nonionic organic compounds [24][25][26][27][28][29] or to improve the photofunctions of photoactive molecules. [30][31][32][33][34] It has therefore been recognised that one of the advantages smectites offer (in addition to the many other important properties of smectites and their intercalation compounds) is that the CEC can be varied in order to control the spatial distribution of organic moieties.…”
Section: Introductionmentioning
confidence: 99%